Hubungan Berat Badan Lahir Rendah dengan Kejadian Asfiksia Neonatorum Di RSUD Bangkinang Kabupaten Kampar - Dewi Rahna Anisa; Harahap, Dewi Anggriani; Erlinawati, Erlinawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Neonatal asphyxia is the failure of a baby to breathe regularly and spontaneously in the first and fifth minutes after the baby is born. Factors that cause neonatal asphyxia include antepartum, intrapartum and fetal factors. The aim of this research was to determine the relationship between low birth weight and the incidence of asphyxia at Bangkinang District Hospital in 2021-2022. This type of research is analytical observational using a Case Control research design. The population in this study is all data on newborns for 2021-2022 as many as 858 babies and the sample population is 89 cases and the control population is 769. The sample in this study uses a 1:1 ratio, that is, after conducting research the sample obtained is 60 with the case sample (babies who experienced asphyxia) and 60 with control samples (babies who did not experience asphyxia). The data collection tool in this research used a checklist sheet. Data analysis in this study used univariate and bivariate analysis. It is known that of the 60 groups of cases (babies who experienced asphyxia) at the Bangkinang District Hospital in 2021-2022, there were 46 babies (77%) born with LBW, of the 60 babies born there were 14 babies born without LBW, and there were 60 babies (100%) who experienced asphyxia, and 60 mothers (100%) of the babies were born without asphyxia. The research results showed that there was a relationship between birth weight and the incidence of asphyxia with a p value (0.003). It is hoped that health services, especially those at the Bangkinang District Hospital, can strive to provide information to village midwives about what Asphyxia is and what factors can cause babies born to experience Asphyxia